Negotiating Power in Public Policy Discourse on Social Media a Critical Discourse Analysis of Government Institutional Posts - Muhammad, Ikmal; Muhamad, Darlisa (Journal of Language Development and Linguistics, 2025)
This study investigates how government institutions use social media as a site of power negotiation in public policy communication. Employing a qualitative approach with Fairclough’s three-dimensional Critical Discourse Analysis and multimodal analysis, data were drawn from 80 purposively selected government account uploads over six months. Systematic coding and interpretive categorization reveal that institutions employ linguistic framing, persuasive rhetoric, and visual semiotics to legitimize authority, foster compliance, and shape public perception, while simultaneously encountering counter-discourses in community interactions. The findings demonstrate that institutional discourse on social media functions not only as policy dissemination but also as a dynamic arena of legitimacy, resistance, and trust-building. This research contributes theoretically to critical discourse studies by linking digital communication and institutional authority, and practically by offering insights for enhancing transparency and public participation in policy communication.